Persepsi Nasabah Terhadap Penerapan Mobile Banking dalam Meningkatkan Pelayanan dengan Menggunakan Metode Technology Acceptance Model: Studi Kasus Bank Rakyat Indonesia Unit Simpong Kota Luwuk, Sulawesi Tengah - Safira Nindita Datu Adam; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine customer perceptions regarding the application of mobile banking in improving bank services. This research method uses quantitative descriptive research methods and uses the Technology Acceptance Model (TAM) theory. The data collection method is carried out by distributing questionnaires online (google form) and documentation in the form. The location of this research is BRI Simpang Unit, Luwuk Banggai, Central Sulawesi. The results of the research show that: 1) Customer perceptions have an influence on improving the services of Bank Rakyat Indonesia Simpang Unit Luwuk City, Central Sulawesi. Thus, the better the perception given by customers, the more it will support the improvement of services at Bank Rakyat Indonesia Simpang Unit Luwuk City, Central Sulawesi; 2) Customer perceptions influence the implementation of mobile banking at Bank Rakyat Indonesia Simpang Unit, Luwuk City, Central Sulawesi. Thus, the better the perception given by customers, the more it will encourage them to use service applications via mobile banking from Bank Rakyat Indonesia Simpang Unit Luwuk City, Central Sulawesi; 3) The implementation of mobile banking has an effect on improving the services of the Bank Rakyat Indonesia Simpang Unit, Luwuk City, Central Sulawesi. Thus, the higher the number of customers who use mobile banking for financial transactions, the more it will reflect the improvement in the service quality of Bank Rakyat Indonesia Simpang Unit Luwuk City, Central Sulawesi; 4) The implementation of mobile banking is able to mediate the influence of customer perceptions on improving services at Bank Rakyat Indonesia Simpang Unit, Luwuk City, Central Sulawesi.